2019
DOI: 10.1111/1754-9485.12894
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective review of CT brain image quality, diagnostic adequacy and radiation dose in a paediatric population imaged at a non‐paediatric tertiary hospital

Abstract: Introduction: Minimising radiation exposure in paediatric imaging examinations whilst maintaining acceptable diagnostic quality continues to present a challenge. The aims of this study were to assess institutional compliance of paediatric CT brain (CTB) examinations performed in an adult hospital with ARPANSA radiation dose recommendations and to compare qualitative CTB diagnostic acceptability with objective imaging parameters and radiation dose. Methods: A retrospective review of 115 consecutive paediatric C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…CTDIvol (mGy) (mean ± SD) DLP (mGy-cm) (mean ± SD) CED (mSv) (mean ± SD) Literature published using modern CT methods since the advent of rapid multi-detector image acquisition, revealed seventeen studies that investigated cumulative ionizing radiation doses from head CT scans in pediatric patients (Figure 1) [1,12,[14][15][16][17][18][19][20][21][22][23][24][25][26][27] . These studies included numerous pediatric patients ranging in age from newborn to 17 years old, with the seventeen studies reporting calculated effective doses ranging from 0.015 mSv to 8.91 mSv [1,12,[14][15][16][17][18][19][20][21][22][23][24][25][26][27] . Of the seventeen studies included, five were found to specifically investigate ionizing radiation exposure from CT scans in pediatric patients with CS, with these studies also emphasizing the utilization of low-dose CT protocols that yielded effective doses of less than 1 mSv [17][18][19][20]26] .…”
Section: Protocolmentioning
confidence: 99%
“…CTDIvol (mGy) (mean ± SD) DLP (mGy-cm) (mean ± SD) CED (mSv) (mean ± SD) Literature published using modern CT methods since the advent of rapid multi-detector image acquisition, revealed seventeen studies that investigated cumulative ionizing radiation doses from head CT scans in pediatric patients (Figure 1) [1,12,[14][15][16][17][18][19][20][21][22][23][24][25][26][27] . These studies included numerous pediatric patients ranging in age from newborn to 17 years old, with the seventeen studies reporting calculated effective doses ranging from 0.015 mSv to 8.91 mSv [1,12,[14][15][16][17][18][19][20][21][22][23][24][25][26][27] . Of the seventeen studies included, five were found to specifically investigate ionizing radiation exposure from CT scans in pediatric patients with CS, with these studies also emphasizing the utilization of low-dose CT protocols that yielded effective doses of less than 1 mSv [17][18][19][20]26] .…”
Section: Protocolmentioning
confidence: 99%
“…11 As all the doses of radiation were converted to mSv, which represent the effective dose received by the patient already taking into account the tissue sensitivity, which enables inter-patient comparison and the calculation of carcinogenesis risk. 12 Where there were absent figures, 2 strategies were adopted: first, to use doses from studies that assessed children and effective dose (mSv) of various radiological and CT investigations 13 (''Literature dose''); secondly, published radiological doses were used as a broad estimate of doses that would have been used locally, a recognized technique 14 (''Local dose''). To test the validity of both, the Literature and Local technique of estimated doses, for the examinations in which an actual dose was present (n ¼ 3049), a comparison was made with the predicted dose.…”
Section: Data Acquisitionmentioning
confidence: 99%